HEALTH PROMOTION PROGRAM AND QUALITY OF LIFE (Fiep Bulletin - online, 2014)
In recent years, companies have adopted programs to promote health with the intention of making the worker healthier, happy and improve their well-being and quality of life (QL), like this prevent diseases. They are other objectives like the reduce costs spent with medical assistance and absence at work and improvement of the productivities. Objective: To investigate the quality of life of employees of a Brazilian state company, participating in a program of physical activity corporate. Methods: It was a sectional study in which participated voluntarily 246 individuals (42.6 ±9.0 years). The QL was evaluated by WHOQOL - Bref questionnaire, which includes four areas: Physical, Psychological, Social Relations and Environment, in addition to two questions overall QL. The maximum score allowed in each area is 20 points - representative of greater satisfaction with the QL. The frequency of physical activity was assessed by Weekly Rate of Training (WRT). The results were expressed by averages and standard deviations. The comparison between the groups was did by Mann-Whitney test (p0.05) when the WRT was considered. This result indicates that the program of promoting health, established by the company's, independent weekly frequency, may be contributing in a positive way to improve the welfare and QL of the employees. Conclusion: Considering the spectrum of variation of scores of the areas evaluated by WHOQOL - Bref, the sample studied, in general, is satisfied with the QL. Other factors, not controlled in the study, may be contributing to the results.
Keywords: Quality of life; satisfaction; Employees